The effect of adding essential oils of cloves and thyme on the performance of local Iraqi goats, digestibility, and rumen fermentation - AL-Galiby, Maitham K. A (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This study aimed to assess the impact of natural essential oils on the performance of native Iraqi goat youngsters, their feed intake, and apparent digestibility. The study comprised 20 male kids of indigenous Iraqi lineage. Their mean weight was 19.72 ± 2.09 kg at three months of age. They were allocated randomly and uniformly into four nutritional interventions. The subjects were provided with a standardized basic diet consisting of 40% alfalfa hay and 60% concentrated feed combination. The kids were nourished in cohorts for 195 days throughout the fattening experiment and for 10 days during the digesting experiment at the conclusion of the study. Nutritional groups comprised: control group on a basic diet, clove group on a basic diet supplemented with 2 ml clove oil, thyme group on a basic diet supplemented with 2 ml thyme oil, and a combined clove and thyme group on a basic diet supplemented with 1 ml clove oil and 1 ml thyme oil. The examined essential oils shown no substantial impact on kids' performance. Clove essential oil markedly enhanced the digestibility of dry matter, organic matter, crude protein, ether extract, acid detergent fiber, and nitrogen balance ratio. The incorporation of thyme oil resulted in a considerable increase in ammonia content within the rumen. Plasma creatinine and low-density lipoprotein concentrations elevated in the thyme group. Incorporating clove or thyme oil into the kids' diet did not enhance the animals' growth performance or blood metabolites. Clove oil exerted a substantial beneficial impact on nutrient digestion. Further investigation is required utilizing elevated doses of clove oil and extended treatment periods.